Building cooperation in peer coaching relationships: understanding the relationships between reward structure, learner preparedness, coaching skill and learner engagement - Ladyshewsky, Richard (Elsevier Ltd, 2006)
This paper outlines several of the key drivers that influence whether learners engage in cooperative, competitive or individualistic behaviour when aligned together in a peer coaching relationship. Reward structures are integral to driving cooperative behaviour. These structures can be implemented by designing instructional activities more strategically, which encourages learners to pursue joint goals while still remaining individually accountable for their performance. Similarly, learner preparedness for peer coaching is critical and skills development is necessary for success. Strategies for reducing the impact of competitive or individualistic behaviour are presented. By examining the literature on cooperative learning, reward structures and peer coaching, this paper provides a practical and evidence-based perspective that will support instructors in developing high-quality cooperative learning systems.